Impairments of Greek government bonds under IAS 39 and IFRS 9: A Case Study - Günther Gebhardt (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
IFRS 9 introduces new impairment rules responding to the G20 critique that IAS 39 results in the delayed and insufficient recognition of credit losses. In a case study of a Greek government bond for the period 2009 to 2011 when Greeces credit rating declined sharply, this study highlights the discretion that preparers have when estimating impairments. IFRS 9 relies more on management expectations and will lead to earlier impairments. However, these appear still delayed and low if compared to the fair value losses.
urn:nbn:de:hebis:30:3-390672
Keywords: 330; IFRS 9; credit losses; government bonds